The role of customer satisfaction on the effect of service quality and corporate image on customer loyalty - Cholisati, Nurifatul; Maesaroh, Eka Siti; Rohman, Fatchur; Puspaningrum, Astrid (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This study tested and analyzed the effect of service quality and corporate image on customer loyalty by mediating customer satisfaction with customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Bondowoso branch. The sample used in this study amounted to 172 respondents with a sampling technique that is purposive sampling. The data analysis used in this study is partial least square with the help of smartpls 3.0 software. The results of this study indicate that all direct influences on each pathway are significant. Customer satisfaction acts as a partial mediation on the effect of service quality and corporate image on customer loyalty.